MEASURES TAKEN IN SCHOOLS DUE TO EPIDEMICS IN THE LATE OTTOMAN AND EARLY REPUBLIC PERIOD - Halide Aslan (Dini Araştırmalar)

(untitled)
Epidemics such as plague, measles, malaria, cholera, and Spanish flu affected the Ottoman Empire in every way, and various measures were taken in various fields according to the conjuncture of the period. The reason for choosing the last period in this study is that more epidemic detections have been made and the records of this period are high. After the 1800s, different epidemics with certain processes and results were experienced in the Ottoman Empire for certain reasons. Some of them affected the state at the micro level and some at the macro level. Undoubtedly, the most affected part of the epidemics were children, especially children of education age, who both accelerated the process of being affected by the disease and became the fastest intervention group. The Ottomans took separate measures regarding education during epidemics. These measures, which include schools, teachers, students, places of residence, and parents from time to time, have had an institutional impact on the state. When we look at the archive documents, issues such as the vacation of schools, vaccination policies, dissemination of disinfection studies, raising awareness among students and their parents, arranging separate allowances for these issues, and financial and moral support of teachers in this regard have been the most mentioned issues regarding epidemic and educational measures. This study, which we will prepare with the document analysis method, mostly based on the Ottoman archive documents and the chronicles of the period, aims to reveal the measures taken by the state to prevent the disruption of education despite the epidemics of the period.